The use of artificial intelligence in the individualization of student learning in higher technical educational institutions - Tverdokhliebova, Natalia; Yevtushenko Nataliіa (Educational Challenges, 2025)
The purpose of this article is to analyze the educational potential of artificial intelligence (AI) in the context of personalized learning, identify the opportunities and advantages of using AI tools for effective integration into the structure of higher technical education, and identify possible limitations and risks associated with this process. The methodological basis of the research is interdisciplinary approaches that include methods of theoretical analysis of scientific sources, digital trends, comparative analysis of adaptive educational platforms (Knewton, Smart Sparrow, ALEKS), as well as empirical analysis and generalization of the experience of implementing AI tools at the National Technical University "Kharkiv Polytechnic Institute". As part of our research, the following results were achieved: the advantages of AI in individualizing higher education were identified, including adaptive platforms, virtual tutors, chatbots, and generative models that support personalized learning, reflection, metacognition, soft skills, and engagement. Risks were also noted: ethical issues, reduced live interaction, teachers’ low digital readiness, digital inequality, reliance on private companies, technical barriers, and insufficient regulation. Practical applications include shaping individual learning trajectories, monitoring progress, supporting microlearning, solving applied tasks with AI assistants, and adapting materials to learners’ needs. Recommendations for phased AI integration involve institutional strategies, infrastructure audits, teacher training, regulatory updates, ethical codes, and interdisciplinary collaboration. The conclusions emphasize that the effective implementation of artificial intelligence in individualized learning in higher technical education is possible only if technological solutions are combined with a humanistic approach, digital culture is developed in the academic environment, and technical, pedagogical, and ethical readiness of participants in the educational process is ensured. In the context of individualized learning, AI may not replace, but rather strengthen, pedagogy, provided that it is humanistically oriented.